An investigation of Arabic speaking learners’ difficulties in the academic writing course - Elmahi, Abdallah (IJRDO- Journal of Educational Research, 2017)
Academic writing skills are of vital importance to the success and complete any academic majorat the university level, yet the development of such skills is a challenge for many Arabicspeaking students, particularly those who graduated from schools where English is not thelanguage of instruction. It is essential to develop and evaluate strategies that can supportacademic writing skills for Arabic speaking students. This qualitative study evaluated a threecredit hours academic English course for academic writing intervention strategy designed tosupport Arabic speaking students at Abu Dhabi University. Data from the course showed twomajor areas of difficulty for participants relating to academic writing: difficulties constructingdifferent types of correct sentences in English, and problems elaborating and supporting newparagraphs ideas in English. The participants showed an improvement in terms of organizationand lay out of essays. Courses like this intervention successfully meet the basic academic needsof Arabic speaking students, although ongoing support is also needed.